Beyond Balanced Growth - Kongsamut, P.; Rebelo, S.; Xie, D. (Review of Economic Studies, 2001)
Balanced growth models are commonly used in macroeconomics because they are consistent with the well-known Kaldor facts regarding economic growth. These models, however, are inconsistent with one of the most striking regularities of the growth process—the massive reallocation of labour from agriculture into manufacturing and services. This paper presents a simple model consistent with both the Kaldor facts and the dynamics of sectoral labour reallocation.